Artificial intelligence and soft computing - Anindita Das Bhattacharjee (Shroff pub. and distributors, 2018)
The course of Artificial Intelligence is taken by all engineering undergraduate and postgraduate students pursuing computer science. Apart from this, it is a popular elective in almost all other branches of engineering. It is also a field chosen for research by many doctoral students. This book has in-depth detail illustration of all the chapters of Artificial Intelligence (AI) with Soft Computing, covering the syllabus of WBUT, Gitam, JNTU, NIT and few different universities. During the course of teaching Artificial Intelligence, the author had found that no textbook covers both Artificial intelligence (AI) with intelligent systems (IS) and soft computing in a comprehensive manner. This book provides a comprehensive coverage of the fundamental concepts and techniques in Artificial Intelligence and Soft Computing with mathematical in depth explanation. The main emphasis is on the solution of real world problems using the latest AI techniques.